Fuga y reintegración del “yo” en el poema “Sueño sónico” de Portals Zubiate - Forsyth Tessey, Paul (2024)
Although the terms “experimentation” and “exploration” are in fact characteristic of the poetic production of an era, in this case, of Peruvian poetry of the nineties, the specific manifestation of both has unprecedented channels in the poetry of Gonzalo Portals Zubiate, as can be seen in the poem “Sonic dream”, included in the book of poetry Ánima insomnia / Sueño sónico (2014), which was written as a four-handed project with Rubén Quiroz Ávila. This essay investigates the “experimental” and “exploratory” manifestation of the “poetic  gaze” (or approach) as constructed in Portals’ poem, in the framework of the book and in relation to the diversity of poetics that characterized the “non-generational” generation of those years, that is, it dives into the function of both phenomena in the poem and the way they are both resolved in the text.